PERLINDUNGAN HUKUM TERHADAP ISTRI MENURUT UNDANG UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Johan Johan (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
Violence can occur within the scope of household members as a whole, not just violent husband on the wife. However, data obtained from both the research and case reports from various institutions that care for women, shows that the majority of cases of domestic violence is the husband of the wife.